2017
DOI: 10.1111/jth.13808
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cell‐based modeling of the royal disease: characterization of the mutated F9mRNA

Abstract: Background The royal disease is a form of hemophilia B (HB) that affected many descendants of Queen Victoria in the 19th and 20th centuries. It was found to be caused by the mutation F9 c.278-3A>G. Objective To generate a physiological cell model of the disease and to study F9 expression at the RNA level. Methods Using fibroblasts from skin biopsies of a previously identified hemophilic patient bearing the F9 c.278-3A>G mutation and his mother, we generated induced pluripotent stem cells (iPSCs). Both the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[ 9 ] Culture conditions mimicking liver development with the sequential addition of specific cytokines and growth factors can drive the differentiation of PSCs into hepatocyte‐like cells (HLCs) expressing specific liver markers such as hepatic nuclear factor 4α (HNF4α) or albumin and displaying hepatocyte‐specific functions. [ 10 , 11 ] To date, a few studies have reported the generation of HB patient–specific iPSCs (HB‐iPSCs) [ 12 , 13 , 14 , 15 , 16 ] and their differentiation into hepatocytes, but further characterization of the clotting FIX produced remains to be done.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Culture conditions mimicking liver development with the sequential addition of specific cytokines and growth factors can drive the differentiation of PSCs into hepatocyte‐like cells (HLCs) expressing specific liver markers such as hepatic nuclear factor 4α (HNF4α) or albumin and displaying hepatocyte‐specific functions. [ 10 , 11 ] To date, a few studies have reported the generation of HB patient–specific iPSCs (HB‐iPSCs) [ 12 , 13 , 14 , 15 , 16 ] and their differentiation into hepatocytes, but further characterization of the clotting FIX produced remains to be done.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, larger minigene construction with multiple exons has been confirmed to be more accurate to reflect the real in vivo splicing outcome of variants due to mimicking the natural genomic context (Acedo et al, 2015; Fraile‐Bethencourt et al, 2017, 2019). Third, a previous study reported an iPSC‐based model of the disease may provide a novel way to investigate the pathogenic mechanism of the splicing site variants at the RNA level (Martorell et al, 2017), especially in F9 with difficulty in ectopic transcription analysis. Fourthly, the clinical and laboratory information of cases carrying the 14 SCVs was collected from our center and F9 variant database, we have some difficulties establishing the relationship between the phenotype and genotype in some cases due to the missing data.…”
Section: Discussionmentioning
confidence: 99%
“…However, few groups have explored its potential for analyzing splicing variants following RT-PCR. 19,20 In this new scenario, the procedure we previously described to analyze the effects of PSSM in VWF 7 has been optimized and adapted to an NGS-based technique to investigate its value in this field. Our main objective was to elucidate the true effects of 18 selected mutations (intronic, synonymous, delins, and missense) on mRNA processing and their genotype/phenotype correspondence by analysis of leukocytes and platelets from clinical samples.…”
Section: Introductionmentioning
confidence: 99%